Challenges in Cooperative Learning Approach in Secondary Social Studies Instruction, Zone 1, Department of Education, Division of Zambales, Philippines - Acosta, Jovelyn E.; De Guzman, Marie Fe (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examines the challenges encountered in implement-ing the cooperative Learning (CL) approach in Secondary Social Studies instruction in Zone 1, Division of Zambales, Philippines. using descriptive research design, survey data were collected from 101 randomly selected Social Studies teachers. Findings indicate that teacher sometimes utilize the CL approach and face challenges related to student engagement, teacher preparation, and assessment methods. The study recommends that teachers explore alternative cooperative learning strategies such as the Tea Party, Carousel, CO-OP CO-OP, and Round Robin methods. Additionally, structured planning and classroom management techniques should be prioritized to enhance the effectiveness of cooperative learning.